The Influence of Religiosity and Islamic Entrepreneurial ‎Literacy on Entrepreneurial Interest in Students of The ‎Sharia Economics Study Program at Mulawarman ‎University - Nazilatul Fitriah; Purwanti Purwanti (FEB Universitas Mulawarman, 2025)
This study aims to determine the effect of religiosity and Islamic en-‎trepreneurial ‎literacy on entrepreneurial interest. This study uses a quantitative ‎approach, This ‎study applies a census method through a questionnaire using ‎Google Forms ‎distributed to the research subjects, namely active students from ‎the 2022-2024 ‎batch of the Sharia Economics study program at Mulawarman ‎University who ‎have taken entrepreneurship courses or have participated in or ‎attended ‎entrepreneurship seminars, business plan boot camps, and the like. ‎Data was ‎collected from 76 respondents and analyzed using ordinal logistic re-‎gression with ‎the help of statistical software. The statistical analysis software ‎used in this study ‎was SPSS version 31, including validity, reliability, model ‎suitability, and ‎hypothesis testing. The independent variables in this study ‎were religiosity and ‎Islamic entrepreneurship literacy, while the dependent ‎variable was interest in ‎entrepreneurship. The results of this study indicate that ‎religiosity and Islamic ‎entrepreneurship literacy have a positive and significant ‎effect on the interest in ‎entrepreneurship among students majoring in Islamic ‎economics at Mulawarman ‎University. The model developed has proven to be ‎feasible for use. High religiosity ‎will strengthen students' belief that ‎entrepreneurship is a positive action that must ‎be taken, while high Islamic ‎Entrepreneurship Literacy will view entrepreneurial ‎behavior as something ‎that is morally and socially supported (in accordance with ‎sharia), thereby ‎resulting in a stronger Interest in Entrepreneurship